Cover Picture: Visualizing Phase Segregation in Mixed‐Halide Perovskite Single Crystals (Angew. Chem. Int. Ed. 9/2019). Issue 9 (29th January 2019) - Mao, Wenxin; Hall, Christopher R.; Chesman, Anthony S. R.; Forsyth, Craig; Cheng, Yi‐Bing; Duffy, Noel W.; Smith, Trevor A.; Bach, Udo
Abstract : Whereas the collective properties of phase‐segregated domains in mixed‐halide perovskites have been well characterized, spectroscopic studies on individual domains have remained elusive. In their Communication on page 2893 ff., T. A. Smith, U. Bach, and co‐workers describe the growth of mixed‐halide perovskite microplatelets and the direct visualization of the growth of I‐rich domains by conventional microspectroscopy techniques. New spectroscopic features provide further insight into the nature of these domains.